The Effectiveness of Counseling Program Based on Existential Therapy in Reducing Future Anxiety Among High School Students - Nayef Alhamad (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
The study aims to identify the effectiveness of a counseling program based on existential therapy in reducing future anxiety among secondary school (Tawjihi) students at male public schools in Irbid during 2018/2019. The study followed quasi-experimental methodology and consisted of 16 male students with high degrees of future anxiety whom were chosen purposefully. The sample was divided into two groups: an experimental group with eight students and a control group of eight students, The researcher used a measure of future anxiety which was composed of (28) items; following its development and ensuring the availability of good means of validity and relaiability that allow its usage.  A developed counseling program based on Frankl's Theory in existential therapy was used. The study found that an existential therapeutic program in reducing future anxiety among experimental group students is effective. The study recommends the importance of expanding the usage of the current counseling program as preventive and therapeutic method to care for secondary school students, helping them in solving their psychological problems, and equpping them with the ability to learn cognitive, intellectual and behavioral skills to reduce future anxiety.